Cognitive Translation Studies: Models and methods at the cutting edge - Xiao, Kairong; Muñoz Martín, Ricardo (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Several indicators seem to suggest that, through nearly six decades of development, Cognitive Translation Studies (CTS) may be taking shape as an autonomous field of study. The main challenges ahead seem to be building sounder theoretical models and carrying out more rigorous methodological scrutiny. These two strands converge as central themes in the 11 contributions to this special issue of LANS-TTS. To provide a context for theoretical modelling and to frame critical discussions of the methods included in this volume, we first trace the present landscape of CTS and how it evolved so as to test Holmes’ criteria for disciplines: founding new channels of communication and sharing a “disciplinary utopia”. The contributions are arranged into four thematic categories as applied to CTS, namely, scientometrics, framing or reframing our field, the reliability and validity of popular research methods, and new methods or novel approaches. This article closes with a call to reflect on some fundamental issues on the next steps of humankind regarding communication, with ever-growing societal demands and expectations that call for refreshing our notions of translation in the context of increasingly diversified forms of multilectal mediated communication.